2023
DOI: 10.1186/s12870-023-04213-y
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of a WRKY transcription factor McWRKY57-like from Mentha canadensis L. enhances drought tolerance in transgenic Arabidopsis

Abstract: Background Drought has become a major environmental problem affecting crop production. Members of the WRKY family play important roles in plant development and stress responses. However, their roles in mint have been barely explored. Results In this study, we isolated a drought-inducible gene McWRKY57-like from mint and investigated its function. The gene encodes a group IIc WRKY transcription factor, McWRKY57-like, which is a nuclear protein with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…6 A-B). Numerous studies have shown that four TF families (MYB, AP2/ERF, NAC, and WRKY) play an important role in the response of plants to drought, temperature, salinity, and other types of abiotic stress [ 34 39 ]. Analysis of the TFs of these four families revealed that drought stress resulted in consistent changes in the expression of most of the common differentially expressed TFs in the leaves of these two apple rootstock varieties, with the exception of NAC ( MD10G1133400 ), WRKY ( MD07G1234700 and MD01G1168600 ), and AP2/ERF ( MD09G1084100 ), which were significantly up-regulated in ‘Jizhen-2’ but significantly down-regulated in ‘ZC9-3’ (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…6 A-B). Numerous studies have shown that four TF families (MYB, AP2/ERF, NAC, and WRKY) play an important role in the response of plants to drought, temperature, salinity, and other types of abiotic stress [ 34 39 ]. Analysis of the TFs of these four families revealed that drought stress resulted in consistent changes in the expression of most of the common differentially expressed TFs in the leaves of these two apple rootstock varieties, with the exception of NAC ( MD10G1133400 ), WRKY ( MD07G1234700 and MD01G1168600 ), and AP2/ERF ( MD09G1084100 ), which were significantly up-regulated in ‘Jizhen-2’ but significantly down-regulated in ‘ZC9-3’ (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have shown that the rapid response of WRKY family genes to drought stress and the rapid upregulation of their expression are beneficial for improving drought tolerance in crops [ 13 , 14 ]. The WRKY family genes ZmWRKY106, ZmWRKY40, McWRKY57-like, TaWRKY1-2D, IgWRKY50 and IgWRKY32 increase the activities of superoxide dismutase (SOD), peroxide dismutase and catalase (CAT) and decrease the content of ROS under drought stress, which helps to reduce the accumulation of H 2 O 2 and MDA and improve the drought tolerance of transgenic plants [ 14 , 15 , 40 , 41 ]. In addition, the AtPOD1, AtCAT1 and AtSOD (Cu/Zn) genes, which are associated with the antioxidant system, were significantly upregulated in TaWRKY1-2D transgenic Arabidopsis plants under drought stress.…”
Section: Discussionmentioning
confidence: 99%
“…A number of family genes have been shown to participate in the regulation of plant drought resistance through the ROS pathway. For example, the mint McWRKY57 enhances the activities of the antioxidant enzymes catalase, superoxide dismutase and peroxidase in transgenic plants and improves drought tolerance [ 14 ]. Overexpression of TaWRKY1-2D enhanced drought tolerance in transgenic Arabidopsis and TaWRKY1-2 silencing in wheat increases the MDA content and reduces the proline and chlorophyll contents as well as antioxidant enzyme activity [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The expression of the McWRKY57 gene was stimulated by mannitol, ABA, and MeJA. Overexpression of McWRKY57-like in Arabidopsis plants considerably improved plant drought tolerance 57 . Additionally, transgenic Arabidopsis lines overexpressing of EjWRKY17 exhibited increased cotyledon greening and root elongation under abscisic acid (ABA) treatment 58 .…”
Section: Discussionmentioning
confidence: 99%